2022
DOI: 10.1002/ael2.20092
|View full text |Cite
|
Sign up to set email alerts
|

Mississippi state and county level yield gap in corn production

Abstract: Continuous corn (Zea mays L.) yield increases are required to promote economic development and support a larger population. Reducing the existing yield gaps is a potential strategy to accomplish this goal. The objective of this study was to evaluate yield trends, and gaps at different production levels in Mississippi using data from 2012 to 2021. Production levels considered were Mississippi yield contest (Yc), Mississippi State University hybrid testing trials under irrigation (Yp) and dryland (Yw), and actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Canola requires high amounts of fertilizer N compared to cereal crops excluding corn (Y. Lin et al., 2020; McGeary et al., 2022; Yahbi et al., 2022). Numerous studies identified that N requirements in canola and other crops differ based on geographic location, soil and climate conditions, and management practices including hybrid selection, tillage practices, and timing of fertilizer application (Dhillon et al., 2022; McGeary et al., 2022). However, previous studies stated that the application of a high N rate only increases the seed yield of canola and reduces nitrogen use efficiency (NUE) (Ahmad et al., 2011; Ma et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Canola requires high amounts of fertilizer N compared to cereal crops excluding corn (Y. Lin et al., 2020; McGeary et al., 2022; Yahbi et al., 2022). Numerous studies identified that N requirements in canola and other crops differ based on geographic location, soil and climate conditions, and management practices including hybrid selection, tillage practices, and timing of fertilizer application (Dhillon et al., 2022; McGeary et al., 2022). However, previous studies stated that the application of a high N rate only increases the seed yield of canola and reduces nitrogen use efficiency (NUE) (Ahmad et al., 2011; Ma et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The yield of maize in the United States has increased with the adoption of improved management practices under irrigated conditions, but yield sensitivity to soil moisture has also increased by 55% (Lobell et al, 2020). In addition, the increased yield gap between irrigated and rainfed systems indicates a sensitivity of maize to low rainfall (Dhillon et al, 2022; Leng, 2021). Studies investigated the impact of drought on crop yield, but prior research has not comprehensively assessed the effects of soil moisture gradients on reproductive, yield, and quality components in maize (Tang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Low rainfall during the critical growth stages often limits crop growth and development in maize‐producing regions, thereby limiting crop yields (Qi et al, 2022; Sah et al, 2020). The likelihood of rainfed maize experiencing suboptimal soil moisture conditions is relatively high, and this can result in a yield loss of up to 78% (Dhillon et al, 2022; Leng, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hand harvesting at the end of the season provides accurate yield data, but it is labor intensive and provides no information for in-season management. Yield data collected at harvest serves only as historical information and has limited utility in future growing season as yield varies temporally and spatially 5,6 .…”
Section: Introductionmentioning
confidence: 99%